Hepatitis B viremia in completely immunized individuals negative for anti-hepatitis B core antibody. Issue 49 (December 2016) - Lai, Ming-Wei; Lin, Tzou-Yien; Liang, Kung-Hao; Lin, Wey-Ran; Yeh, Chau-Ting
Abstract : Abstract: The presence of anti-hepatitis B virus (HBV) core antibody (anti-HBc) is considered a sensitive lifetime marker of HBV infection. Here, we examined this dogma by investigating the prevalence of hepatitis B viremia in anti-HBc negative complete vaccines in Taiwan. A total of 795 participants (1.7–20.0 years old) had completed HBV vaccination in infancy and were anti-HBc negative. Serum samples were available for 460 individuals with isolated anti-HBV surface antibodies (anti-HBs) (HBsAg-negative and anti-HBc negative) and for 245 individuals who tested negative for all 3 markers (triple seronegative). All samples were submitted for polymerase chain reaction (PCR) targeting both the preS/S and X/pre-C gene regions. Of the 460 participants with isolated anti-HBs, 26 (5.65%) were positive for HBV by 2-target PCR. Of the 245 triple seronegative samples, 12 (4.90%) were positive for HBV DNA. In the former group, the prevalence of viremia was significantly higher in individuals aged 6 to 10 years than in all other ages combined (11.82% vs 3.7%, P = 0.001). The anti-HBs titers were significantly lower in participants 6 to 10 years old than in all other ages combined (72.06 vs 99.64 mIU/mL, P = 0.038). In total, 7 (0.99%) subjects had quantifiable HBV DNA levels (280–18, 820 IU/mL). Sequence analysis of the S gene revealed vaccine escape like mutations. H epatitis B viremia can occur in completely vaccinated individuals who are negative for anti-HBc. Abstract : Supplemental Digital Content is available in the text